Inter-District Variation in Anthropometric and Body Composition Characteristics of Adolescent Male Basketball Players from Uttar Pradesh, India: A Multivariate, Age Adjusted Cross-Sectional Analysis - Singh, Akash; Singh, Prof. Abhimanyu (International Journal of Aquatic Research and Environmental Studies, 2026)
Stature, limb length, and lower-limb muscularity are recognised determinants of basketball performance and figure prominently in talent identification, yet comparative, multivariate, age-adjusted data for Indian adolescent male players are scarce. To profile and compare selected anthropometric and body-composition characteristics among inter-district adolescent male basketball players from seven district squads in Uttar Pradesh, India, using a multivariate framework while statistically adjusting for chronological age. Eighty male basketball players (mean age 16.64 ± 1.32 years) representing the BHU, BLW, Agra, Pilibhit, Gorakhpur, Gautam Buddh Nagar (GBN), and Varanasi squads were assessed for standing height, leg length, arm length, thigh and calf girths, and seven skinfolds. The sum of skinfolds (ΣSF) and relative body fat (Slaughter youth equation) were derived. After verifying normality (Shapiro–Wilk) and homogeneity of variance (Levene's test), a one-way MANOVA tested the overall district effect, followed by univariate ANOVAs with eta-squared and Tukey HSD; a one-way ANCOVA with age as a covariate confirmed robustness. Significance was set at p < 0.05. MANOVA revealed a significant overall district effect (Wilks’ Λ = 0.004, F₄₂,₃₁₈ = 17.61, p < 0.001; multivariate η² = 0.61). Univariate tests showed significant differences for height (p = 0.004, η² = 0.22), leg length (p < 0.001, η² = 0.31), thigh girth (p < 0.001, η² = 0.31), calf girth (p = 0.003, η² = 0.23), and ΣSF (p < 0.001, η² = 0.28), but not arm length or estimated body fat. All five effects persisted after age adjustment (ANCOVA, all p ≤ 0.003). GBN players were the tallest and longest-legged, BHU players carried the greatest thigh girth, and Pilibhit players showed the highest ΣSF. Adolescent male basketball players across the sampled districts share a homogeneous relative-adiposity profile but diverge robustly in linear dimensions and lower-limb girths, independent of age. The findings provide multivariate, age-adjusted baseline reference data to inform region-sensitive talent identification and conditioning.
Keywords: Basketball; Anthropometry; Body Composition; Skinfolds; Adolescent athletes; MANOVA; ANCOVA; Talent Identification